2010
DOI: 10.1155/2010/906163
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Cinacalcet in MEN1 Hyperparathyroidism

Abstract: Background. Management of multiple-endocrine neoplasia type 1- (MEN1-) associated hyperparathyroidism is associated with high recurrence rates and high surgical morbidity due to multiple neck explorations. Cinacalcet, a calcimimetic agent licensed for the treatment of secondary hyperparathyroidism and parathyroid carcinoma, may provide a medical alternative for the management of these complex patients. Methods. A prospective audit was performed of eight patients; three males and five females, aged 20–38 at dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 13 publications
3
38
2
1
Order By: Relevance
“…Although MEN1-related PHPT patients are likely the best candidates for a medical treatment, the effectiveness of cinacalcet in MEN1 has been poorly investigated, probably due to low frequency of the disorder that is estimated in two to ten cases per 100 000 in the general population. Indeed, three different studies described the efficacy of cinacalcet in a total of 11 patients (10,11,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MEN1-related PHPT patients are likely the best candidates for a medical treatment, the effectiveness of cinacalcet in MEN1 has been poorly investigated, probably due to low frequency of the disorder that is estimated in two to ten cases per 100 000 in the general population. Indeed, three different studies described the efficacy of cinacalcet in a total of 11 patients (10,11,12).…”
Section: Discussionmentioning
confidence: 99%
“…According to the European Medicines Agency (EMA) prescription labeling, cinacalcet is indicated for the treatment of patients with secondary HPT due to chronic kidney disease, patients with PHPT due to parathyroid carcinoma, and patients with PHPT meeting the criteria for parathyroidectomy who have contraindications to surgery or persistent PHPT after surgery. Although MEN1 patients are good candidates for a medical treatment, the effectiveness of cinacalcet has been so far reported in 11 patients described in three different studies (10,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Cinacalcet has been effectively used to lower serum calcium levels in patients with MEN1-associated PHPT, a condition in which the rate of a successful surgery is lower than in the sporadic forms of PHPT (79,80).…”
Section: Rct 1amentioning
confidence: 99%
“…Cinacalcet hydrochloride has been approved for the treatment of hypercalcemia in patients with parathyroid carcinoma and in primary HPT patients unable to undergo surgery [54]. Three separate studies have reported its effectiveness in 11 MEN1 patients [54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Three separate studies have reported its effectiveness in 11 MEN1 patients [54][55][56]. Cinacalcet is also the only available potent calcimimetic for the management of secondary HPT [57].…”
Section: Discussionmentioning
confidence: 99%